Upaya Meminimalkan Adanya Disparitas dalam Penjatuhan Putusan Pemidanaan dalam Perkara Tindak Pidana Korupsi di Indonesia - Metya Mutiara Cahyani (Fakultas Hukum Universitas Andalas, 2024)
Problems regarding the execution of sentences obtained for corruptors recently become attractive spotlight in the eyes of the public. In the debate, many sentences for corruptors are the center of the general debate because there is a tendency for corruptors to have sentences that are considered light with the losses caused by these corruptors. Especially if they find significant differences in sentences (disparities), for corruption cases which are more or less the same and worthy of comparison. Therefore, it is necessary to know the factors of the large number of disparities in the sentencing of corruption and efforts are needed to zoom out or deal with it. This research was compiled using normative legal research, namely research based on legal materials (library based) which focuses on reading and studying primary and secondary legal materials. The approach in this study is a comparative legal approach (comparative law approach). Factors that continue to influence the emergence of disparities in the imposition of criminal convictions on Corruption Crime Cases in Indonesia are influenced by the legal system, legislation in Indonesia, factors originating from the judges themselves, factors originating from criminal events, and factors arising from not the existence of joint rules/guidelines in the imposition of sentencing